PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM PERUSAHAAN INDUSTRI BATUBARA - Sinski Natasya Ardana Reswari; Sri Hasnawati (CV. Syntax Corporation Indonesia, 2023)
The development of the capital market as an investment tool institution has economic and financial functions that are increasingly needed by the public as an alternative media and fundraiser. At present capital market products are considered as an investment alternative so that this sector recorded satisfactory growth from 2015 to November 2020 reaching more than 3.6 million investors. One of the sectors listed on the Indonesia Stock Exchange (IDX) is a company engaged in the mining sector because of its role as a provider of energy resources that are very necessary for a country's economic growth. The energy sector has various sub-sectors and industries, one of which is the coal industry. This industry is one of the biggest contributors in the energy sector. Coal industry companies are companies that have contributed the most to the number of companies in the energy sector on the IDX. Of course, this absorbs many investors to invest in one of these mining companies in the hope of getting a return on the investment made. The purpose of this study was to examine the effect of profitability, capital structure liquidity and company size on stock returns. This research is a quantitative research with secondary data with a sample of 33 companies. Data analysis was carried out starting from normality, multicollinearity, autocorrelation and heteroscedasticity tests. While the other tests are multiple linear regression analysis, F test, T test and test of the coefficient of determination. The results of this study note that Profitability has no effect on stock returns, Liquidity is known to have a positive effect on stock returns, Capital structure has an effect on stock returns and Firm size has no positive effect on stock returns